ExoFrontiers : big questions in exoplanetary science - Madhusudhan, Nikku (IOP (Series). Release 21., 2021)
This book is a compendium of key scientific questions, challenges, and opportunities across different areas of exoplanetary science. The field is currently experiencing rapid growth, and the book provides a front-row view of the advancements at the cutting-edge of the field. Each chapter contains a short exposition on the most important open questions, challenges, and opportunities in a specific area from the perspective of one or more top experts in the area. It provides a starting point for researchers, experts and non-experts alike, to obtain a quick overview of the forefront of exoplanetary science and a vision for the future of the field.